GROWTH PERFORMANCES OF LOBSTER JUVENILE (Cherax quadricarinatus) FED WITH SILKWORM AND RICE FLOUR - kurniawan, andri; Adibrata, Sudirman; Lingga, Rahmad; Setiadi, Jhodi; Wulandari, Ufi Ayu; Hidayah, Reysya S N (Journal of Aquatropica Asia, 2024)
Freshwater lobster (Cherax quadricarinatus) is one of the freshwater commodities that has the potential to be cultivated and has economic value. However, the problem still faced by farmers is the quality of feed which can affect low growth and survival. This research aims to analyze the growth performance of juvenile lobsters fed silk worms and rice flour. This research used 30 juvenile lobster samples measuring 1-3 cm (+ 1 inch) that were around 30 days old per aquarium. The parameters observed were body length, body weight, and survival rate (SR) of juvenile lobsters and the water parameters measured were pH, temperature, and total dissolved solids (TDS). The results of the research show that juvenile freshwater lobsters are able to consume silk worms and rice flour so that juvenile lobsters can be classified as omnivores. Feeding treatment in the form of a combination of silk worms and rice flour showed the best results for growth in length, weight and SR of juvenile freshwater lobsters. Juvenile growth during 32 days of rearing fed a combination of silkworm and rice flour resulted 4.30 cm + 0.02 cm in a length, 1.43 g + 0.01 g in weight, and SR 80%.